NILAI-NILAI PENDIDIKAN IBADAH DALAM NOVEL RINDU KARYA TERE LIYE - Saindah Saindah; Aslan Aslan; Dewi Ferawati (CV. ADIBA ASIHA AMIRA, 2025)
Worship education is the process of guiding and directing all the potential that already exists in humans or students, especially the potential for servitude to God, so that it will cause obedience that is firmly embedded in the heart as a guide and foundation for life both in this world and in the hereafter based on the Qur’an and Hadith. This research is designed using a qualitative approach with the type of library research. The data analysis technique used in this research is content analysis, which draws conclusions through efforts to find the messages contained in the novel Rindu. The results showed that: 1) The value of Mahdhah worship education consists of: prayer, fasting, and Hajj, while the value of Ghairu Mahdhah worship education consists of: alms, learning, dhikr and helping. 2) The application of the value of worship education in the family consists of: habituation of prayer and ablution, while the application of the value of worship education at school consists of: habituation to pray, praying in congregation, and read the Qur’an